Catalytic surface development of novel nickel plate catalyst with combined thermally annealed platinum and alumina coatings for steam methane reforming - Obradović, Ana; Likozar, Blaž; Levec, Janez (International journal of hydrogen energy, 2013)
Catalytically active surface of small nickel (min 99 wt%) plates for steam methane reforming was enhanced by successive temperature programmed oxidation−reduction (TPO−TPR) pretreatment and combined physical vapor deposition of Pt and Al2O3. The effect of annealing time, temperature, order and number of coatings on the catalytic activity was investigated by means of a pulse technique at the reaction temperature of 760 °C. The most active and stable surface phases resulted after the successively deposited layers of Pt, Al2O3, and Pt had been annealed for 12 h onto 2-cycle TPO−TPR pretreated nickel plate at the temperature of 700 °C in a circulating atmosphere of N2. The durability performance of the so-prepared surface phases on a specifically structured plate catalyst element (diameter 43 mm and length 42 mm) was tested in a tubular reactor for some 70 h in temperature range 500−650 °C. Deactivation was mainly caused by carbon surface deposition. Structured nickel (Ni) plate catalyst for steam methane reforming (SMR) with enhanced activity by platinum (Pt) and alumina (Al2O3) coating. [Display omitted] ► Catalytic enhancement of structured Ni-plate reforming catalyst was investigated. ► Oxidation–reduction process and deposition of Pt and Al2O3 were done on Ni plates. ► Catalytic activity of enhanced Ni-plate samples was tested by pulse technique. ► Structured Ni-plate catalyst was examined in continuous differential reactor. ► Catalyst deactivation at conditions chosen was caused mainly by carbon deposition.